FATIGUE CRACKING OF CEMENTITIOUSLY STABILIZED PAVEMENT LAYERS THROUGH LARGE-SCALE MODEL EXPERIMENTS - Casmer, Jeffrey (My University, 2011)
The objective of National Cooperative Highway Research Program (NCHRP) Project 04-36 was to recommend laboratory procedures to measure performance related characteristics of pavement layers stabilized with cement, lime, and fly ash and to provide validated distress models to be incorporated into the Mechanistic-Empirical Pavement Design Guide (MEPDG). As part of this project, the objective of this study was to identify a procedure for determining the number of load cycles to fatigue crack initiation for cement-stabilized base course and subgrade materials using a Large-Scale Model Experiment (LSME). This procedure was intended to provide a validation for the newly calibrated MEPDG fatigue model by replicating field conditions. Additionally, a series of unconfined compressive strength (UCS) tests were conducted to provide a Level 2 correlation between UCS and several MEPDG performance model inputs. Initial LSMEs consisted of silt-cement (4% by weight) layers approximately 1 m x 1m and 0.2-m-thick. Surface and subgrade deflections were measured and the stabilized layer monitored for fatigue cracking. Changes in the deflection characteristics were expected to manifest during or after cracking of the materials. Cracking was not observed after 325,000 cycles at loads ranging from 11.1 ? 31.1 kN. A second silt-cement layer of the same geometry was tested next. To increase deflections during loading and thus increase stress/strain in the layer, a piece of extruded polystyrene (XPS) was placed beneath the stabilized layer. The presence of the foam layer more than doubled the elastic deflections compared to the first experiment. Even with the increase in deflections, no cracking was observed after 140,000 cycles at 17.8 kN and 260,000 cycles at 22.2 kN. For subsequent experiments, the geometry of the stabilized layer was changed to approximately 1 m x 2 m and 0.1-m-thick. Recycled pavement material (RPM) was stabilized with 3% cement by weight and supported on a 1 m x 1 m, 25-mm-thick layer of XPS. The applied load ranged from 15.6 ? 26.7 kN. After about 179,000 cycles at 26.7 kN, a fatigue crack was observed on the RPM surface. Deflection data gave no clear indication of the exact time of crack initiation. Another layer of gravel and cement (3% by weight) was set up in the same configuration. The applied load was set to 26.7 kN at the beginning of the experiment. Two fatigue cracks were observed on the gravel surface in less than 5,000 cycles. Like the RPM experiment results, the deflection data for gravel-cement appeared unchanged by the presence of these cracks. For the next gravel-cement specimen the XPS layer was removed and the applied load reduced to 20.0 kN for more than 900,000 cycles. The load was increased to 26.7 kN for an additional 400,000 cycles. A crack was observed just prior to 400,000 cycles. Deflection results were difficult to interpret and there was an equipment malfunction during this experiment causing some uncertainty in the results. Three silt-cement layers (8% by weight) were placed on an expanded polystyrene (EPS) support with the same geometry as the previous RPM and gravel layers. The first silt-cement layer cracked in less than 200 cycles at 6.7 kN. For the second layer the applied load was reduced to 4.0 kN and a crack was observed at ? 3,000 cycles. The third layer was subjected to a load of 3.3 kN. Small cracks (2.5-cm-long) were observed after 1,500 cycles. The cracks continued to grow and connect to additional observed cracks. After 16,000 cycles, the cracks appeared to be forming a ring around the steel load plate. As with the previous LSMEs where cracking was observed, the deflection data provided no indications of the exact time of crack initiation. Results from the final two silt-cement LSMEs were used to attempt a validation of the fatigue model incorporated into MEPDG. The unknown regression coefficients (k1 and k2) were first calibrated using laboratory beam fatigue tests. The tensile stress at the bottom of the stabilized layer in the LSME was determined from the finite element program MichPAVE, simulating the LSME setup. The applied stress ratio was calculated by dividing the MichPAVE calculated stress by modulus of rupture (MR) obtained from the beam tests. This stress ratio was used with the calibrated fatigue model to predict the number of cycles to cracking and compared to the observed number of cycles to cracking from the LSME. Alternatively, the observed number of cycles to cracking was used as a model input to predict the required stress ratio and compared to the stress ratios calculated from the MichPAVE analysis. Both techniques did not provide a good validation of the model calibration. Cracking during both LSMEs of silt-cement was observed prior to 20,000 cycles and the model predicted cycles to cracking in excess of 100,000 cycles. MichPAVE predicted stress ratios were 38% and 24% for the second and third silt-cement LSMEs, respectively. Fatigue model predictions of stress ratio ranged from 69% to 123%. Unconfined compressive strength tests were conducted on gravel, sand, silt, and clay stabilized with cement, lime, and fly-ash. Nine of the possible twelve different mix combinations were tested. Lime-stabilized sand and gravel, along with clay-fly ash were omitted from testing as unlikely combinations. The combination of silt-lime required the addition of Class F fly ash to produce a stabilized mixture. The 28-d UCS for cement stabilized mixtures ranged from 3.6 ? 4.5 MPa. Cement content ranged from 3% for gravel to 12% for clay and were based on the minimum amount to achieve 7-d strength of 2.1 MPa. Fly ash content of 13% by weight was used for gravel, sand, and silt based on FHWA and MEPDG strength recommendations. Materials stabilized with fly ash were subjected to a 7-d accelerated cure at 40?C. The UCS after 7-d accelerated curing ranged from 0.63 ? 2.0 MPa, with gravel-fly ash having the highest strength. Clay-lime (6% by weight) had a 7-d accelerated UCS of 1.03 MPa and silt-lime-fly ash (4% lime, 12% fly ash by weight) 1.87 MPa. The results of the UCS study will be used in the model development phase of NCHRP Project 4-36. The results of this study show the deformational performance of stabilized layers are not affected by fatigue cracking in the LSME. There does not appear to be any changes in the deflection data corresponding to observed cracks. Fatigue behavior of stabilized layers is controlled by stress conditions and material defects. As a result, cracking does not always occur at the location of maximum stress but at local weak points. Also, performance of the stabilized layer in the LSME provided a poor validation for the calibrated fatigue model coefficients based on preliminary laboratory beam fatigue data due to material variability. Therefore, the LSME will not provide usable results for fatigue model validation. Correlation of UCS to MR for gravel-cement and silt-cement proved similar to current MEPDG recommendations. Additional MR testing will be conducted to determine the correlation with UCS for incorporation into MEPDG.